The amino and carboxyl domains of the infectious bronchitis virus nucleocapsid protein interact with 3′ genomic RNA - Zhou, Minglong (Virus Res, 2000)
Previous studies indicated that the nucleocapsid (N) protein of infectious bronchitis virus (IBV) interacted with specific sequences in the 3′ non-coding region of IBV RNA. In order to identify domains in the N protein that bind to RNA, the whole protein (409 amino acids) and six overlapping fragments were expressed as fusion polypeptides with six histidine-tags. Using gel shift assays, the intact N protein and amino polypeptides, from residues 1 to 171 and residues 1 to 274, and carboxyl polypeptides, extending from residues 203 to 409 and residues 268 to 407, were found to interact with positive-stranded IBV RNA representing the 3′ end of the genome. The two (32)P-labeled probes that interacted with N and the amino and carboxyl fragments of N were RNA consisting of the IBV N gene and adjacent 3′ non-coding terminus, and RNA consisting of the 155-nucleotide sequences at the 3′ end of the 504-nt 3′ untranslated region. In contrast, the polypeptide fragment from the middle region, residues 101–283, did not interact with these 3′ IBV RNAs. The binding site in the amino region of N was either not present or only partially present in the first 91 residues because no interaction with RNA was observed with the polypeptide incorporating these residues. Cache Valley virus N expressed with a histidine tag, bovine serum albumin, and the basic lysozyme protein did not shift the IBV RNA. The lower molarities of the carboxyl fragment compared with residue 1–274 fragment needed for equivalent shifts suggested that the binding avidity for RNA at the carboxyl domain was greater than the amino domain.